Effect of freezing and storage on serum vitamin D levels measured by mass spectrometry and immunoassay in reproductive age women - Jennifer K. Y. Ko; Sammy P. L. Chen; Kevin K. W. Lam; T. O. Chan; Raymond H. W. Li; Ernest H. Y. Ng (Scientific Reports)
Abstract The objective of this study was to assess the effects of freezing and storage on serum vitamin D levels in women undergoing ovarian stimulation for in vitro fertilization and in the natural cycle. This is a prospective observational in vitro study in a tertiary reproductive medicine center and an accredited hospital-based Chemical Pathology Laboratory. Each serum sample was divided into equal volume aliquots and stored at -20oC and −80oC. The samples were analyzed for 25-hydroxyvitamin D [25(OH)D] levels using liquid chromatography‒mass spectrometry and immunoassay at baseline and after 2 weeks and 7 months of storage. The overall serum 25(OH)D levels measured by liquid chromatography‒mass spectrometry showed a statistically significant reduction over 7 months of storage at -80 °C [median % change: -4.9 (25th, 75th percentile: -10.1, 2.5), p = 0.020] but not at -20 °C compared with the baseline. With the immunoassay, the overall serum 25(OH)D levels also significantly decreased over 7 months of storage at -80 °C [median % change: -4.0 (25th, 75th percentile: -15.6, 1.4), p < 0.001] but not at -20 °C compared with the baseline. In conclusion, the 25(OH)D levels of the serum samples stored at -20oC and − 80oC were lower at 7 months of storage when compared with baseline levels, but the difference was small. Nevertheless, vitamin D deficiency is usually assessed based on clinical thresholds. Awareness of potential degradation of 25(OH)D is needed, and the method used for measurement should be taken into account when interpreting retrospective studies of 25(OH)D using archived serum samples, as even small variations can lead to women being ‘reclassified’ into different vitamin D status categories.